THE UTILIZATION OF DIGITAL MARKETING FOR MICRO, SMALL, AND MEDIUM ENTERPRISES - Setiawan, Edi; Irawan, Oki; Ulza, Emaridial; Zamzany, Faizal Ridwan (The journal of contemporary issues in business and government, 2021)
The purpose of this study was to find out the benefits of the implementation of digital marketing for MSMEs in Jakarta. The applied method was a quantitative approach using a descriptive-analytical method. Samples were taken using a random sampling technique with a total sample of 200 MSMEs. However, those that meet the criteria were 112 MSMEs. The results showed that the sales variable and awareness variable simultaneously had a significant effect on the digital marketing-understanding variable.